What is the link between malaria prevention in pregnancy and neonatal survival in Nigeria? (2019)
Neonatal mortality has been recognized as a global public health challenge and Nigeria has the highest prevalence in Africa. Malaria during pregnancy jeopardizes neonatal survival through placental parasitaemia, maternal anaemia, and low birth weight. This study investigated association between the malaria prevention in pregnancy and neonatal survival using a nationally representative data - Nigeria Demographic Health Survey 2013. Child recode data was used and the outcome variable was neonatal death. The main independent variables were the use of at least 2 doses of intermittent preventive treatment in pregnancy with sulfadoxine-pyrimethamine (IPT-SP) and proportion of pregnant women who reported Insecticide Treated Net (ITN) use the night before the survey. Data were analyzed using Pearson Chi-square (x 2 ) test of association and survival analysis techniques. Total neonatal mortality rate was 38 per1000 live births. Cox proportional hazard model showed that low birth weight (HR 1.49, 95% CI (1.15 – 1.93 p=0.003) and adequate number of ANC visits (≥ 4 visits) (HR 0.68, 95% CI (0.53 – 0.93) were associated with neonatal survival. The use of at least 2 doses of IPT-SP was not an independent factor for neonatal survival (HR 0.72, 95% CI (0.53 – 1.15). Malaria prevention in pregnancy is crucial for neonatal survival through the prevention of low birth weight.